(untitled) (Biodiversitas Journal of Biological Diversity, 2015)
Suratman, Ari Pitoyo, Sri Mulyani, Suranto. 2015. Assessment of genetic diversity among soursop (Annona muricata) populations from Java, Indonesia using RAPD markers. Biodiversitas 16: 247-253. The objective of this study was to determine genetic diversity of the soursop (Annona muricata L.) populations from Java (Indonesia) using RAPD markers. A total of 70 individuals were collected from 7 soursop populations, distributed along the geographical range of natural distribution in Java. Genetic diversity was estimated by RAPD technique using 6 arbitrary selected primers. Those primers produced 151 polymorphic bands with the percentage of polymorphism for each primer ranged from 95% to 100%. The genetic diversity value (h) within each population ranged from 0.0418 to 0.0525. The highest h value (0.0525) was found in the KRA population whereas the lowest h value was observed in the PCT population. The highest genetic distance value (0.0410) was observed in SKH-GKD populations pair whereas the lowest genetic distance value (0.02448) was estimated in KRA-PCT populations pair. Based on the dendogram, the seven soursop populations were segregated into three major clusters. The first cluster consisted of SKH, KRA, PCT, NGW, and KPG populations. The GKD population was then grouped into second cluster. In the third cluster, the BGR population was grouped separately and more genetically distant than the others. However, the relationship dendrogram showed that the grouping did not always indicate the geographical origins similarity, but possibly showed the genetic similarity.